2021
DOI: 10.3390/su131810429
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-Energy Analysis and Life Cycle GHG Emissions Assessments of Innovative Earth-Based Bamboo Plastering Mortars

Abstract: Biomaterials and raw earth have demonstrated a promising potential for improving various thermal properties of plastering mortars used in buildings. The objective of this research was the evaluation of the thermal-energy performances and life cycle greenhouse gas (GHG) emissions of different mixtures of engineered, bio-based earth mortars composed of bamboo particles, earth, and different cementitious materials. Four mixtures were assessed: mortars without bamboo particles (matrix), and mortars containing 3%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…No intuito de avaliar a representatividade de cada insumo e de cada categoria de impacto, conforme já explicado, os dados foram normalizados. Analisando os resultados notou-se que ao contrário do que se esperava com base na revisão da literatura (7,10,11,12,13,14,15,16,17) , a categoria de Aquecimento Global não foi a mais representativa. Ressalta-se que o conjunto de normalização da CML baseline é do ano de 2000, por isso, é preciso considerar que em anos diferentes as emissões podem ser consideravelmente divergentes em virtude das atividades humanas e densidade demográfica do ano tomado como referência.…”
Section: Resultsunclassified
“…No intuito de avaliar a representatividade de cada insumo e de cada categoria de impacto, conforme já explicado, os dados foram normalizados. Analisando os resultados notou-se que ao contrário do que se esperava com base na revisão da literatura (7,10,11,12,13,14,15,16,17) , a categoria de Aquecimento Global não foi a mais representativa. Ressalta-se que o conjunto de normalização da CML baseline é do ano de 2000, por isso, é preciso considerar que em anos diferentes as emissões podem ser consideravelmente divergentes em virtude das atividades humanas e densidade demográfica do ano tomado como referência.…”
Section: Resultsunclassified
“…Caldas et al [92] further showed that both wood bio-concrete and bamboo bio-concrete, using a LCA, could achieve a carbon-negative status if considered as a replacement for Portland cement for SCMs (supplementary cementitious materials). Similarly, adding bamboo particles to plastering mortars can significantly reduce greenhouse gas (GHG) emissions, as the carbonation, carbon sequestration, and storage processes of bamboo, although still slightly carbon-positive, are low enough to considerably contribute to GHG reduction [94]. Paiva et al [94] further reported that mortar made with a greater portion of bamboo particles presented a greater potential for GHG reduction and better thermal performance due to a lowered thermal conductivity in the bamboo end product.…”
Section: Carbon Storage In Bamboo Productsmentioning
confidence: 99%
“…Finally, one strategy especially important for embodied carbon reduction is using bio-based material as reinforcements since these materials can sequester and store CO 2 , which can be used for adobe, Cob, RE, and LSC. Additionally, they bring extra benefits in thermal performance and operational energy reduction during building operation for airconditioning [14,15] and help combat crack propagation, directly related to the durability and service life of buildings' components.…”
Section: Research Outlooks and Recommendationsmentioning
confidence: 99%
“…Paiva et al [14,15] evaluated the potential of earth-based mortar reinforced with bamboo fibers to reduce GHG emissions. Using bamboo fibers reduces the mortar's thermal conductivity, improves building thermal-energy performance, and stocks CO 2 , reducing life cycle GHG emissions.…”
Section: Introductionmentioning
confidence: 99%